DESIGN AND DEVELOPMENT OF A CARBON FOOTPRINT MOBILE APPLICATION FOR UNIVERSITY STUDENTS - Yee, Chee Ling (Universiti Malaysia Sarawak (UNIMAS), 2020)
Global warming is a reality and it evolves into a whole bunch of issues, therefore, the focus research has become on the ways to reduce carbon emission effectively. Carbon footprint is the carbon dioxide emissions that are caused by a person's daily activities that could contribute to global warming. University students nowadays have strong knowledge and attitudes toward carbon footprint but they less practice it in their daily life. Thus, this research conducted to increase their awareness toward carbon footprint by developing a mobile application. The mobile application can calculate users’ carbon footprint from a transportation aspect. The simple interaction design model is used to develop this mobile application which including identifying needs and establishing requirements, developing alternatives designs, building interaction versions of the designs and evaluating designs. After completing the design mobile application, an evaluation is conducted on the mobile application by conducting cooperative evaluation among five respondents who are university students aged between 20 to 25 years old. Usability testing is also used to evaluate the usability of the mobile application by the same respondents after the interactive mobile application prototype is done. Out of five respondents, three of them satisfied with the design of the mobile application and the other two respondents were unsatisfied with the design of the mobile application.